ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA PROCESADORA Y COMERCIALIZADORA DE TILAPIA EN FILETES EN LA CIUDAD DE PORTOVELO, PROVINCIA DE EL ORO - Valdiviezo Lima, Mariuxi Jasmin (2018)
The objective of this investment project is to determine the technical and commercial feasibility for the implementation of a processing and marketing company of tilapia fillets in the City of Portovelo. Following a procedure with the use of techniques and instruments such as the survey applied to the families of the Population of the City of Portovelo, facilitating the development of the research, which served to achieve the proposed objectives. The most important contents of the project that are taken into account in its structure are the following: In the market study, the effective demand of 205,031 pounds of tilapia fillet and the offer of 8,100 pounds (considering fresh whole tilapia as an offer) was obtained, obtaining a difference between the two variables of 196,931. In the marketing plan strategies were proposed in order to reach the consumer market with a quality product. As for the technical study, the annual installed capacity was 43,800 pounds, the annual used capacity was 20,800 pounds, that is, in a daily production of 80 pounds of tilapia fillet and the optimal location of the company in the City of Portovelo. The organizational study of the company, is constituted as a sole proprietorship company of limited responsibility, in addition the organizational structure of the same one is determined, that is to say, the requirements for its legalization, permissions, registries and manual of functions for the employees. The investments in fixed assets for the project are quantified in $ 2,754.00 dollars, investment in deferred assets $ 1,340.00 dollars and working capital of $ 9,684.40 5 dollars. Then the total investment is $ 13,778.40 dollars, for the realization of the project you will obtain a financing of $ 7,000.00 dollars, at an interest rate of 12%, granted by Ban Ecuador. The financial evaluation was based on the cash flow that provides the information necessary for the application of the following indicators: VAN of $ 31,165.73 dollars, based on the Minimum Acceptable Rate of Return TMAR, which is calculated taking into account the active interest rate, country risk and annual inflation, giving us as a result 13.49%; TIR of 85.18%; Analysis of Sensitivity in the increment of the Costs will resist the changes in a 9.50% and a sensitivity of 0.99; and in the decrease of the income of 8.20% and with a sensitivity of 0.99, being positive values that do not affect the profitability of the project; Benefit Ratio Cost that for each dollar invested you get 16 cents of return, and Period of Recovery of Capital 1 year, 6 months, 5 days.